Peran Lembaga Amil Zakat, Infaq dan Shadaqah Muhammadiyah (Lazismu) dalam Membantu Perekonomian Masyarakat Provinsi Sulawesi Tenggara - Budiman, Arman; Faisal Nasier, Muhamad; Annisa Fitri, Nur (Alif Lam : Journal of Islamic Studies and Humanities, 2024)
Starting from the unstructured Lazismu work program for Southeast Sulawesi Province, resulting in funds not being distributed appropriately to the community (both Muhammadiyah cadres and non-Muhammadiyah cadres) in the end the funds that should have been distributed were only stagnant in the institution's account, even though if you look at the amount of the funds it is based on the Lazismu report Southeast Sulawesi for period 2 for 6 months the funds are quite large. In relation to poverty, the method used in this research is field research, using a qualitative approach intended to examine a situation or phenomenon comprehensively, rationally and systematically, as well as looking at possible relationships between variables in looking at the problems determined in a study. The results of this research  To minimize poverty, taking into account the nominal amount of lazismu income in Southeast Sulawesi Province, the author provides suggestions for performance to increase and be more targeted in distribution, the program offers are: Distribution of educational scholarships, humanitarian aid, health costs, increasing salaries Honoraria, Distributing funds to young people who are hampered by panic money, Friday Blessings, Activating Lazismu social media accounts.